Enhancing the piezoelectric properties of flexible hybrid AlN materials using semi-crystalline parylene. (24th February 2017) - Jackson, Nathan; Mathewson, Alan
Abstract: Flexible piezoelectric materials are desired for numerous applications including biomedical, wearable, and flexible electronics. However, most flexible piezoelectric materials are not compatible with CMOS fabrication technology, which is desired for most MEMS applications. This paper reports on the development of a hybrid flexible piezoelectric material consisting of aluminium nitride (AlN) and a semi-crystalline polymer substrate. Various types of semi-crystalline parylene and polyimide materials were investigated as the polymer substrate. The crystallinity and surfaces of the polymer substrates were modified by micro-roughening and annealing in order to determine the effects on the AlN quality. The AlN crystallinity and piezoelectric properties decreased when the polymer surfaces were treated with O2 plasma. However, increasing the crystallinity of the parylene substrate prior to deposition of AlN caused enhanced c -axis (002) AlN crystallinity and piezoelectric response of the AlN. Piezoelectric properties of 200 °C annealed parylene-N substrate resulted in an AlN d 33 value of 4.87 pm V −1 compared to 2.17 pm V −1 for AlN on polyimide and 4.0 pm V −1 for unannealed AlN/parylene-N. The electrical response measurements to an applied force demonstrated that the parylene/AlN hybrid material had higher V pp (0.918 V) than commercial flexible piezoelectric material (PVDF) ( V pp 0.36 V). The results in this paper demonstrate that the piezoelectric properties of a flexible AlN hybrid material can be enhanced by increasing the crystallinity of the polymer substrate, and the enhanced properties can function better than previous flexible piezoelectrics.